2008
DOI: 10.1108/14635770810915931
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking: methods and tools for SME

Abstract: PurposeThe purpose of this paper is to present a benchmarking process that can assist small to medium‐sized enterprises (SME).Design/methodology/approachThe paper describes how the steps of a benchmarking process can be positioned with the steps of the plan‐research‐observe‐analyzes‐adapt‐improve cycle (PROAAI) and shows that the tools proposed to carry out these steps are mostly reserved for big companies. We therefore detail a set of tools and methods to assist SMEs in the deployment of the steps of a benchm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…2008 [32] Setting tools and methods to assist SMEs in the deployment of the steps of a benchmarking process (plan-researchobserve-analyzes-adapt-improve cycle).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2008 [32] Setting tools and methods to assist SMEs in the deployment of the steps of a benchmarking process (plan-researchobserve-analyzes-adapt-improve cycle).…”
Section: Discussionmentioning
confidence: 99%
“…Maire et al [32] proposed a set of tools and methods especially targeted at: 1) the description of the processes (process to be improved and reference process) using the description of the current practices used (Observe step); and 2) the comparison of these processes, leading to suggestions of improvements to carry out on the process to improve (Analyze step). They indicated that the steps of the planresearch-observe-analyzes-adapt-improve cycle are mostly reserved for big companies, therefore detailed observe and analyze steps should add as a set of tools and methods to assist SMEs in the deployment of the steps of a benchmarking process.…”
Section: Current Benchmarking Modelsmentioning
confidence: 99%
“…In other words benchmarking can be utilized as a catalyst between development and innovation [12]. Benchmarking has been exercised extensively in large companies, but it has been widespread to small and medium enterprises (SMEs) [13]. Study shows that benchmarking, which has previously been commonly used in large companies, cannot be fully adopted by SMEs [13].…”
Section: Literature Study 21 Use Of Benchmarking In Smesmentioning
confidence: 99%
“…Niemi and Huiskonen (2008) focus their benchmarking process model on internal benchmarking, which makes the methodology somewhat less suited for SMEs that typically lack the size to justify internal benchmarking between different company units. Maire et al (2008) follow a plan-research-observe-analyze-adapt-improve sequence of benchmarking steps and target their process model explicitly toward SME usage. All approaches aim at providing a clear and stable referential frame of process steps to be followed, but the variety of process models proposed counters that very same intention: an SME wishing to embark on benchmarking for the first time has a plethora of process models to choose from.…”
Section: Approaches To Sme Logistics Benchmarking – Literature Reviewmentioning
confidence: 99%